Novel small-molecule electron donor for solution-processed ternary exciplex with 24% external quantum efficiency in organic light-emitting diode. Issue 7 (7th May 2019) - Zhao, Juewen; Zheng, Caijun; Zhou, Yu; Li, Chuan; Ye, Jun; Du, Xiaoyang; Li, Wan; He, Zeyu; Zhang, Ming; Lin, Hui; Tao, Silu; Zhang, Xiaohong
Abstract : Efficient solution-processed exciplex OLEDs were developed by incorporating a novel small molecule electron-donor and utilizing the strategy of ternary exciplexes. Abstract : Considering their characteristics of thermally activated delayed fluorescence (TADF), exciplexes have great potential in achieving organic light-emitting diodes (OLEDs) with 100% internal quantum efficiency. However, the widely reported vacuum-deposited exciplexes still have not realized satisfactory efficiencies. Since stronger intermolecular interactions can be induced during solution processing, solution-processed exciplexes may be better candidates. In this work, we designed and synthesized a novel small-molecule electron donor (4-(9-(perfluoropyridin-4-yl)-9 H -fluoren-9-yl)- N, N -diphenylaniline, TPA-3) with good solubility and film-forming ability. Combined with PO-T2T ((1, 3, 5-triazine-2, 4, 6-triyl)tris(benzene-3, 1-diyl)tris(diphenylphosphine oxide)) as an electron acceptor, the solution-processed exciplex OLED based on TPA-3:PO-T2T achieved a high maximum external quantum efficiency (EQE) of 14.4%. Furthermore, two other electron donors that can also form exciplexes with PO-T2T were separately added to TPA-3:PO-T2T to form ternary exciplexes. The additional reverse intersystem crossing channel in the higher energy exciplex was beneficial for the unitization of triplet excitons. Consequently, a solution-processed exciplex OLED was achieved with a remarkable maximum EQE of 24%. To the best of our knowledge, this result is the best performance reported to date for exciplex OLEDs fabricated via either the solution processing or vacuum deposition method. The outstanding feature presented herein can provide a good reference for the future development of high-efficiency exciplex OLEDs.